2017
DOI: 10.1101/cshperspect.a029884
|View full text |Cite
|
Sign up to set email alerts
|

Omics and Exercise: Global Approaches for Mapping Exercise Biological Networks

Abstract: The application of global "-omics" technologies to exercise has introduced new opportunities to map the complexity and interconnectedness of biological networks underlying the tissue-specific responses and systemic health benefits of exercise. This review will introduce major research tracks and recent advancements in this emerging field, as well as critical gaps in understanding the orchestration of molecular exercise dynamics that will benefit from unbiased omics investigations. Furthermore, significant rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 82 publications
0
52
0
Order By: Relevance
“…Our observation of only a subset of mTOR targets may reflect temporal dynamics, as this kinase is fully activated one hour post‐contraction (O'Neil et al , ), whereas we collected muscle immediately after the completion of the contraction protocol. Other divergences between species and exercise modes may be attributed to differences in central catecholamine release or delivery of circulating factors to the exercising muscle and muscle fiber type composition resulting in potential alterations in cellular composition (Hoffman, ). In situ contraction of isolated muscle has several advantages as an exercise model including the ability to override cognitive and neural factors to produce controlled, regular contractions to the point of muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of only a subset of mTOR targets may reflect temporal dynamics, as this kinase is fully activated one hour post‐contraction (O'Neil et al , ), whereas we collected muscle immediately after the completion of the contraction protocol. Other divergences between species and exercise modes may be attributed to differences in central catecholamine release or delivery of circulating factors to the exercising muscle and muscle fiber type composition resulting in potential alterations in cellular composition (Hoffman, ). In situ contraction of isolated muscle has several advantages as an exercise model including the ability to override cognitive and neural factors to produce controlled, regular contractions to the point of muscle fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Several areas are likely to continue to advance the field of exercise biology and subsequent innovations in training practices. The first is the direct application of the various ''omics'' technologies to map exercise networks in a holistic, unbiased, and integrated manner and to identify how various cells and organs contribute to adaptation in response to different training interventions (Hoffman, 2017;Hoffman et al, 2015). While targeted, reductionistbased approaches laid the foundation for our understanding of distinct biological mechanisms regulating exercise responses , the complexity and integrated nature of the whole-body exercise warrant global, unbiased system approaches to unravel the interwoven networks underlying training adaptation.…”
Section: Reviewmentioning
confidence: 99%
“…While targeted, reductionistbased approaches laid the foundation for our understanding of distinct biological mechanisms regulating exercise responses , the complexity and integrated nature of the whole-body exercise warrant global, unbiased system approaches to unravel the interwoven networks underlying training adaptation. As the field of omics and exercise continues to expand, new opportunities arise for exercise biologists to collaborate and unravel the intricate nature of training responses that have not been achievable without these global approaches (Hoffman, 2017). By identifying novel training-induced proteins and kinases, it is possible that specialized training modalities can be implemented to selectively target these exercise-regulated pathways.…”
Section: Reviewmentioning
confidence: 99%
“…Given myofilament proteins play a key role in force generation and skeletal muscle function, these results raise the possibility that age-dependent phosphorylation of myofilament proteins could contribute to age-related muscle dysfunction (63). Beyond the effects of aging that can be associated with sarcopenia, Hoffman et al (30) studied global phosphorylation induced by acute exercise in human skeletal muscle. The author used isobaric labeling and phospho-peptide enrichment techniques to quantitatively analyze phosphorylation changes and showed that 1,004 unique, exercise-regulated phospho-sites could be detected on 562 proteins.…”
Section: Posttranslational Modification Of Proteins In Human Skeletalmentioning
confidence: 99%